Significance of m6A regulatory factor in gene expression and immune function of osteoarthritis - Xie, Xiaoyan; Zhang, Yun; Yu, Jian; Jiang, Feng; Wu, Chuyan (Frontiers in Physiology, 2022)
One of the most prevalent post-transcriptional modifications of eukaryotic mRNA is the RNA N6-methyladenosine (M6A) regulator, which plays a significant role in a range of illnesses. The involvement of m6A regulators in osteoarthritis (OA) is not fully known at this time. By comparing non-osteoarthritic and osteoarthritic patients, 26 significant m6A regulators were identified from the gene expression omnibus GSE48556 dataset. Seven candidate M6A regulators (IGFBP3, WTAP, IGFBP1, HNRNPC, RBM15B, YTHDC1, and METTL3) were screened using a random forest model to assess the likelihood of osteoarthritis. A column line graph model founded on seven M6A modulator candidates was created. Patients might profit from the column line graph model, according to decision curve analysis. Based on chosen relevant m6A modifiers, a consensus clustering approach was utilized to categorize osteoarthritis into 2 m6A categories (group A and group B). To measure the m6A pattern, a principal component analysis technique was created to generate the m6A score for every sample. Cluster A patients exhibited greater m6A scores than cluster B patients. Furthermore, we discovered that patients with lower and higher m6A scores had varied immunological responses using m6A type. Finally, m6A regulators contribute significantly in the progression of osteoarthritis. Our research on m6A patterns might help to guide further osteoarthritis immunotherapeutic techniques.